Potential and limitations of the application of school distance education in Greece, through the views of teachers - Αμοργιανιώτη Ειρήνη (Ανοικτή Εκπαίδευση: το περιοδικό για την Ανοικτή και εξ Αποστάσεως Εκπαίδευση και την Εκπαιδευτική Τεχνολογία, 2022)
This present study focuses on the views of secondary school teachers about the potential of implementing school distance education in Greece. During the spring of 2020, due to the pandemic of Covid-19, distance education filled the gap created by the suspension of operation of school units. An empirical research was conducted on ten teachers in the prefecture of Ioannina using the semi-structured interview tool. The research findings show that teachers value positively the free access and flexibility provided by distance education. It is also noteworthy that they believe that school distance education should be institutionalized to meet emergencies. However, they are wary against self-sufficient distance education in conditions other than emergencies. Finally, they consider that supplementary use is in some cases necessary to support knowledge and consider that mixed education can be used in adults courses or in children who are absent due to health reasons.